2018
DOI: 10.1002/2017gl075795
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity of Arctic Liquid Clouds to Long‐Range Anthropogenic Aerosol Transport

Abstract: The rate of warming in the Arctic depends upon the response of low‐level microphysical and radiative cloud properties to aerosols advected from distant anthropogenic and biomass‐burning sources. Cloud droplet cross‐section density increases with higher concentrations of cloud condensation nuclei, leading to an increase of cloud droplet absorption and scattering radiative cross sections. The challenge of assessing the magnitude of the effect has been decoupling the aerosol impacts on clouds from how clouds chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 77 publications
1
55
0
Order By: Relevance
“…These observations indicate that changes in T and RH of air masses entering the Arctic will likely have a very large influence on observed CF, to a degree that is much more regionally important than the microphysical effects of the aerosols themselves. In line with previous studies (e.g., Gryspeerdt et al (2016);Coopman et al (2018)), these results also underscore the need for large sample volumes to identify 5 systematic differences in regional air masses between clean and all conditions, and a way to reduce the confounding effects of meteorological co-variation on these samples. To accomplish this, we analyzed over 10 million profiles across the Arctic Ocean, which were binned into similar T and RH groups.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…These observations indicate that changes in T and RH of air masses entering the Arctic will likely have a very large influence on observed CF, to a degree that is much more regionally important than the microphysical effects of the aerosols themselves. In line with previous studies (e.g., Gryspeerdt et al (2016);Coopman et al (2018)), these results also underscore the need for large sample volumes to identify 5 systematic differences in regional air masses between clean and all conditions, and a way to reduce the confounding effects of meteorological co-variation on these samples. To accomplish this, we analyzed over 10 million profiles across the Arctic Ocean, which were binned into similar T and RH groups.…”
Section: Discussionsupporting
confidence: 74%
“…This finding suggests that aerosol microphysical impacts on clouds are more influential at the lower temperatures and/or more stable conditions over sea ice. Previous studies have also observed larger aerosol microphysical effects under more stable conditions in the Arctic (Coopman et al, 2018;Zamora et al, 2017). Possible reasons for the disparate behavior at different altitudes are discussed below.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…When the impact of meteorology is controlled for, these satellite‐based ACI estimates indicate a high sensitivity of Arctic clouds to transported aerosol, though anthropogenic sources appear to make a larger impact than aerosol from biomass burning (Coopman et al, , ). This high sensitivity of Arctic clouds could not solely be explained by overall lower aerosol concentrations compared to lower latitudes and may arise in part due to the strong stability of the Arctic troposphere that inhibits vertical mixing (Coopman et al, ). Importantly, these satellite‐based ACI estimates rely upon comparison to a clean cloud background state and use modeled carbon monoxide concentrations as a proxy for aerosol.…”
Section: Aerosol‐cloud Interactionsmentioning
confidence: 99%
“…Later studies stress the complexity of this mechanism and its efficiency in different geographic locations. For example, Coopman, Garrett, et al () using multiyear satellite, meteorological, and tracer transport model data found that low‐level Arctic cloud response to anthropogenic aerosols are 2 to 8 times higher than in lower latitudes and that the role of biomass aerosols to Arctic clouds response have been overstated in previous studies. Consequently, the relative contribution of aerosol to the radiative forcing of Arctic clouds is still highly uncertain (Coopman, Riedi, et al, ; Flanner, ; Garrett et al, ; Garrett et al, ; Norgren et al, ; Solomon et al, ; Wylie & Hudson, ; Zamora et al, ; Zhao & Garrett, ).…”
Section: Introductionmentioning
confidence: 99%